High-resolution icosahedral reconstruction: fulfilling the promise of cryo-electron microscopy. - Mancini, E; de Haas, F; Fuller, S (1997)
Two recent papers have defined the secondary structure of the hepatitis virus capsid using a combination of cryo-electron microscopy and icosahedral image reconstruction. These two papers do more than reveal a new fold for a virus protein; they herald a new era in which image reconstruction of single particles will provide reliable high-resolution structural information. In revealing the promise of these techniques to the structural biology community, their two papers should play a seminal role for single particle work, similar to that of the work of Unwin and Henderson on bacteriorhodopsin in revealing the potential of electron microscopy of membrane protein crystals. Indeed, the success of these single particle methods owes much to the development of high-resolution techniques for two-dimensional crystals. This review will summarize some of the history of icosahedral reconstruction from cryo-electron micrographs, compare the two different approaches used to obtain the recent results and outline some of the challenges and promises for the future.